CONTROLLING OF INVESTMENT PROGRAMS OF ELECTRIC ENERGY COMPANIES - N. Gryzunova; I. Kiseleva; A. Tramova (Вестник Северо-Кавказского федерального университета)
Controlling investments allows us to evaluate the effectiveness of numerous projects included in the investment programs of the electric power industry. In the context of sanctions, lockdown and funding sources, the focus in analytical research is shifting to a mix of investment value assessments, as well as to the use of an interdisciplinary approach. For example, investment efficiency and balancing of debtors ' and accounts payable, controlling the standards of effective turnover of assets and accounts payable, and controlling the level of investment risk. These are all key tools for ensuring the long-term solvency and stability of the company and the investment program and the startup. The purpose of the article is to reveal the possibilities of controlling investments of electric power companies using a profile accounting system. Various tools of controlling and technological price audit were used in the work. The use of the results of the internal technological price audit of investment programs within the framework of controlling systems of electric power companies to ensure their long-term efficiency is the main module ofthe financial policy oftop management. Investment audit and controlling allow us to maintain international standards of investment eiciency throughout the entire business cycle. The results of the article have the potential for successful theoretical and practical application in the process of organizing the controlling of investments, receivables and payables in the company; and they can become part of the methodological tools of companies. The proposed investment-controlling algorithm allows preventing inefficient investments.